Towards 2057 setting the national agenda : dimensions for change (original documents) (Penerbit Universiti Malaysia Terengganu, 2009)
The main purpose of the project is thus to generate insights and input from Malaysians of various backgrounds to be forwarded to the new leadership for consideration in charting the future direction of the country